Guided inquiry improves undergraduate students psychomotor skills in gram staining practicum - Nadya Treesna Wulansari; Ni Wayan Kesari Dharmapatni; I Putu Gede Sutrisna; Anak Agung Istri Mas Padmiswari; Kadek Buja Harditya; Ida Ayu Manik Damayanti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Gram staining of bacteria is an important practical material in Microbiology and Parasitology courses as part of Basic Nursing Science. This technique is widely used for the initial identification of pathogenic microorganisms. However, observations indicate that some students have not mastered the Gram staining technique optimally, leading to difficulties in interpreting microscopic findings. Until now, practical learning has been dominated by demonstration and one way instruction methods, so that the development of students' psychomotor skills has not been optimal. This study aims to evaluate the effectiveness of the guided inquiry method in improving the psychomotor skills of nursing students in Gram staining practical. The study used a quasi experimental design with a pretest–posttest control group design. The research subjects were students of the Nursing Study Program, semester II of the 2025/2026 Academic Year, consisting of two classes, namely the guided inquiry class (70 students) and the control class (72 students). Psychomotor skill data were analyzed based on the difference between posttest and pretest scores. The difference in psychomotor skill improvement between the two groups was analyzed using the Independent Samples t-test at a significance level of 0.05. The results showed a significant difference in the difference in psychomotor skill scores between the guided inquiry group and the control group, with the guided inquiry group having a higher average score. This indicates that guided inquiry learning is effective in improving students' psychomotor skills in Gram staining practicums.Abstrak. Pewarnaan Gram pada bakteri merupakan materi praktikum penting dalam mata kuliah Mikrobiologi dan Parasitologi sebagai bagian dari Ilmu Keperawatan Dasar. This technique is widely used for the initial identification of pathogenic microorganisms, so mastering these psychomotor skills is essential for students to ensure the accuracy of clinical diagnoses. Namun, pengamatan menunjukkan bahwa sebagian mahasiswa belum menguasai teknik pewarnaan Gram secara optimal, sehingga menimbulkan kesulitan dalam menafsirkan temuan mikroskopis. Hingga saat ini, pembelajaran praktikum masih didominasi oleh metode demonstrasi dan pengajaran satu arah, sehingga pengembangan keterampilan psikomotorik mahasiswa belum optimal. Penelitian ini bertujuan untuk mengevaluasi efektivitas metode inquiry terarah dalam meningkatkan keterampilan psikomotor mahasiswa keperawatan pada praktikum pewarnaan Gram. Penelitian ini menggunakan desain kuasi-eksperimental dengan desain pretest–posttest kelompok kontrol. Subjek penelitian adalah mahasiswa Program Studi Keperawatan, semester II Tahun Akademik 2025/2026, yang terdiri dari dua kelas, yaitu kelas inquiry terarah (70 mahasiswa) dan kelas kontrol (72 mahasiswa). Data keterampilan psikomotor dianalisis berdasarkan selisih skor posttest dan pretest. Perbedaan peningkatan keterampilan psikomotor antara kedua kelompok dianalisis menggunakan Uji-t Sampel Independen pada tingkat signifikansi 0,05. Hasil menunjukkan adanya perbedaan yang signifikan pada selisih skor keterampilan psikomotor antara kelompok pembelajaran inquiry terarah dan kelompok kontrol, dengan kelompok pembelajaran berbasis penyelidikan terpandu memiliki skor rata-rata yang lebih tinggi. Hal ini menunjukkan bahwa pembelajaran berbasis inquiry terarah efektif dalam meningkatkan keterampilan psikomotorik siswa pada praktikum pewarnaan Gram.